Cytokine adsorption during ex vivo blood perfusion improves contractility of donation after circulatory death hearts - Saemann, Lars; Pohl, Sabine; Wachter, Kristina; Georgevici, Adrian-Iustin; Köhler, Conny; Jünger, Jennifer; Hoorn, Fabio; Gharpure, Nitin; Großkopf, Anne; Korkmaz-İçöz, Sevil; Wenzel, Folker; Karck, Matthias; et al. (Journal of the American Heart Association, 2024)
Background - Donation after circulatory death (DCD) hearts have to withstand ischemia/reperfusion injury that is partially driven by proinflammatory cytokines and decreases ventricular contractility. We hypothesize that cytokine adsorption during normothermic ex vivo blood perfusion of DCD hearts reduces the cytokine levels and improves ventricular contractility. - Methods and Results - Porcine DCD hearts were maintained 4 hours by ex vivo blood perfusion with (DCD‐BPCytoS, all groups: N=8) or without (DCD‐BP) CytoSorb, followed by 2 hours reperfusion with fresh blood, including left ventricular functional analysis using a balloon catheter. In a control and a DCD group, hearts were evaluated after procurement. We determined lactate and cytokines after ex vivo blood perfusion and the myocardial and left anterior descending artery transcriptome using microarrays after reperfusion. In DCD‐BPCytoS, the developed pressure (control: 124±7 mm Hg/s, DCD: 86±4 mm Hg/s, DCD‐BP: 69±11 mm Hg/s, DCD‐BPCytoS: 112±9 mm Hg/s; P<0.05) and maximal slope of pressure increment (control: 2010±39 mm Hg/s, DCD: 1219±164 mm Hg/s, DCD‐BP: 964±163 mm Hg/s, DCD‐BPCytoS: 1794±205 mm Hg/s; P<0.05) were higher compared with DCD‐BP and DCD hearts. However, contractility decreased later during reperfusion without CytoSorb. After 4 hours, troponin, lactate (45±5% versus 69±9%, P<0.05), IL (interleukin)‐1β, ‐1ra, and ‐8 were lower in DCD‐BPCytoS hearts. In the myocardium of DCD‐BPCytoS compared with DCD‐BP hearts, inflammatory mediator receptor activity/binding pathways were enriched, and pathways for collagen‐containing extracellular matrix and contractile fiber were underrepresented. In the left anterior descending artery of DCD‐BPCytoS hearts, serine/threonine/tyrosine kinase activity and wound‐healing pathways were enriched, and mitochondrial protein‐containing complex and respiratome‐associated pathways were underrepresented. - Conclusions - CytoSorb during ex vivo blood perfusion enhances the maintenance of DCD hearts and is likely to improve graft function after transplantation.
Gesehen am 16.06.2025